Why do so many incompetent men become leaders? - Chamorro-Premuzic, Tomas (Harvard Business Review Press, 2019)
Marshaling decades of rigorous research, Chamorro-Premuzic points out that although men make up a majority of leaders, they underperform when compared with female leaders. In fact, most organizations equate leadership potential with a handful of destructive personality traits, like overconfidence and narcissism. In other words, these traits may help someone get selected for a leadership role, but they backfire once the person has the job